Size‐dependent evolution of phonon confinement in colloidal Si nanoparticles. (4th June 2015) - Zhang, Pengfei; Feng, Yu; Anthony, Rebecca; Kortshagen, Uwe; Conibeer, Gavin; Huang, Shujuan
Abstract : A size‐dependent evolution of phonon confinement is revealed in Si nanoparticles (NPs) via Raman spectroscopy. By introducing a variable confinement factor, α, into a well‐known phenomenological phonon confinement model (PCM) developed by Richter et al., acceptable fits are achieved to downshifted and asymmetrically broadened Raman spectra of Si NPs with different diameters, d, from 2.4 nm to 6.3 nm. A comparative study using Raman spectra of colloidal Si NPs, for the first time, shows an apparent positive linear correlation between α and the Si NP size. Based on the PCM, the amplitude of the atomic vibration (phonon) at the real physical boundary of NPs is proportional to e −α/2, which indicates that the amplitude of the first order optical phonon is relatively larger at the edges for smaller Si nanostructures despite of their stronger phonon confinement weighed by α/d 2 . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Size evolution of a phonon confinement rule is explored via Raman spectroscopy within Si nanoparticles (NPs). By calculating the introduced confinement factor, α, through successful fitting to Raman spectra of Si NPs with different sizes, an apparent positive linear correlation between α and the Si NP size was revealed.